2021
DOI: 10.1038/s41438-021-00471-9
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Magnolia biondii Pamp. provides insights into the evolution of Magnoliales and biosynthesis of terpenoids

Abstract: Magnolia biondii Pamp. (Magnoliaceae, magnoliids) is a phylogenetically, economically, and medicinally important ornamental tree species widely grown and cultivated in the north-temperate regions of China. Determining the genome sequence of M. biondii would help resolve the phylogenetic uncertainty of magnoliids and improve the understanding of individual trait evolution within the Magnolia genus. We assembled a chromosome-level reference genome of M. biondii using ~67, ~175, and ~154 Gb of raw DNA sequences g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 81 publications
14
38
1
Order By: Relevance
“…Thus, these indicated that all four magnoliid species experienced a λ multiplication event about 120 million years ago. This point was consistent with previously sequenced genomes of M. biondii , L. chinense , C. kanehirae, and L. cubeba ( Chaw et al., 2019 ; Chen et al., 2019 , 2020b ; Dong et al., 2021 ). While the Ks values of one-to-one orthologs analysis of M. officinalis with L. chinense , C. kanehirae and L. cubeba were 0.13, 0.75, and 0.76, respectively.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, these indicated that all four magnoliid species experienced a λ multiplication event about 120 million years ago. This point was consistent with previously sequenced genomes of M. biondii , L. chinense , C. kanehirae, and L. cubeba ( Chaw et al., 2019 ; Chen et al., 2019 , 2020b ; Dong et al., 2021 ). While the Ks values of one-to-one orthologs analysis of M. officinalis with L. chinense , C. kanehirae and L. cubeba were 0.13, 0.75, and 0.76, respectively.…”
Section: Resultssupporting
confidence: 92%
“…Based on the phylogenetic tree constructed by 365 single-copy genes, we found that the magnoliids were as sister groups to the eudicots and monocots. Together with the two genomes of Magnoliaceae ( M. biondii and L. chinense ) previously published, our phylogenomic analyses all indicated that magnoliids were independent of monocots and eudicots, which was consistent with the results observed in previous studies ( Chen et al., 2019 , 2020a ; Dong et al., 2021 ; Hu et al., 2019 ; Rendón-Anaya et al., 2019 ).
Figure 4 The Phylogenetic tree including 14 species was constructed based on 365 single-copy genes The WGD shared between the Magnoliales and Laurales is indicated with a red star, and the purple box indicated that an extra recent WGD event was experienced in the Laurales.
…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations